Escenarios conceptuales, contextuales, normativos y metodológicos para fortalecer la convivencia escolar en el marco de una pedagogía para la paz. (2014)
In this paper the problem of violence school is addressed by focusing on the conceptual, contextual, normative and methodological elements to understand challenges of the school to realize the need for the culture of peace from a pedagogy of conflict.